Relationship between global leadership initiative on malnutrition (GLIM) defined malnutrition and survival, length of stay and post-operative complications in people with cancer: A systematic review. Issue 3 (March 2023) - Brown, Dylan; Loeliger, Jenelle; Stewart, Jane; Graham, Kate L.; Goradia, Sunita; Gerges, Chantal; Lyons, Shania; Connor, Molly; Stewart, Sam; Di Giovanni, Adrian; D'Angelo, Sarah; Kiss, Nicole
Summary: Background & aims: The predictive validity of the GLIM criteria for survival, length of hospital stay (LOHS) and post-operative complications among people with cancer have not been systematically reviewed. This systematic review aims to determine whether GLIM malnutrition is predictive of these outcomes, and whether the predictive validity is affected by how phenotypic and etiologic criteria are assessed. Methods: Cohort studies published after 2018 were systematically reviewed according to PRISMA guidelines from Embase, Medline Complete and CINAHL Complete. Risk of bias and methodologic quality were assessed using the Journal of the Academy of Nutrition and Dietetics' Quality Criteria Checklist tool for Primary research. Results: In total, 21 studies were included, including 28, 726 participants. All studies investigated survival, where 18 reported GLIM malnutrition is associated with decreased survival. LOHS was investigated in six studies, with all finding an association between GLIM malnutrition and longer LOHS. Post-operative complications were assessed in seven studies, of which five reported GLIM malnutrition was predictive of increased post-operative complications. Methods to assess the GLIM phenotypic and etiologic criteria varied, with consistent predictive ability for survival regardless of method of assessing reduced muscle mass. However, predictive ability was more variable across different measures of inflammation and reduced intake. Conclusion: GLIM malnutrition was consistently predictive of worse clinical outcomes. Different measures of reduced muscle mass did not affect the predictive ability of GLIM for survival. However, variation in assessment of the etiologic criteria resulted in varying predictive ability of the GLIM diagnosis for survival.